2022
DOI: 10.1101/2022.01.14.22269108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Application of a Force Sensor during Sit-to-Stands to Measure Dynamic Cerebral Autoregulation Onset

Abstract: Purpose: Current sit-to-stand methods measuring dynamic cerebral autoregulation (dCA) do not capture the precise onset of the time delay (TD) response. Reduced sit-to-stand reactions in older adults and individuals post-stroke could inadvertently introduce variability, error, and imprecise timing. We applied a force sensor during a sit-to-stand task to more accurately determine how TD before dCA onset may be altered. Methods: Middle cerebral artery blood velocity (MCAv) and mean arterial pressure (MAP) were m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Interactions of aging and age-related vascular health with cerebrovascular autoregulation under behavioral conditions, e.g. aerobic exercise (Palmer et al, 2022) and positional transfers (Sorond et al, 2010; Whitaker et al, 2022), may explain the presence of this CBF hypoperfusion effect immediately after exercise in older adults in the present study. Older individuals may possess poor age-related cerebrovascular regulation under states of physiologic stress (Claassen et al, 2021; Ward et al, 2018), which are differentially regulated across brain regions and between individuals (Brassard et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
“…Interactions of aging and age-related vascular health with cerebrovascular autoregulation under behavioral conditions, e.g. aerobic exercise (Palmer et al, 2022) and positional transfers (Sorond et al, 2010; Whitaker et al, 2022), may explain the presence of this CBF hypoperfusion effect immediately after exercise in older adults in the present study. Older individuals may possess poor age-related cerebrovascular regulation under states of physiologic stress (Claassen et al, 2021; Ward et al, 2018), which are differentially regulated across brain regions and between individuals (Brassard et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
“…While previous studies have shown the ability to implement an accelerometer to detect the angle and speed of the sit-to-stand, [8][9][10][11][12][13][14] we are the first to implement a custom force sensor to improve the temporal accuracy of the TD response. 15 Our methodology uses a force sensor to simultaneously measures the sit-to-stand reaction time with the physiological dCA response. 15 We have reported on the ability to implement a force sensor to identify a defined moment of transition between sitting and standing, or arise-and-off (AO).…”
Section: Introductionmentioning
confidence: 99%
“…15 Our methodology uses a force sensor to simultaneously measures the sit-to-stand reaction time with the physiological dCA response. 15 We have reported on the ability to implement a force sensor to identify a defined moment of transition between sitting and standing, or arise-and-off (AO). 15 Traditionally, the TD response is calculated from the time in which individuals are verbally told to stand up from a seated position.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations